ENHANCING STUDENTS' SOCIAL SKILLS THROUGH A GROUP TECHNOLOGY - BASED PROJECT IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2017)
The aim of the study is to reveal students' attitudes towards a group assignment including physical activity and moderntechnologies in Physical Education. Almost a hundred of secondary school students participated in the study. The studentscompleted a specific group task that goal was to create a video exercise according to specific criteria. The anonymousquestionnaire was designed to get the feedback from the students regarding the learning outcomes, participation, evaluation andattitudes towards such a project in PE. Data was analysed by percentage calculation. As a result, a majority of the students thinkthat they learned about the composition and improved their social skills and relationship with their team members through theproject.
Keywords: Quality Physical Education; group assignment; social skills; technology